Implementasi Kegiatan Menghafal Al-Quran Untuk Guru dan Karyawan SMP IT Al Banna Natar - Rudiansyah, Firman (STIT Darul Fattah Bandar Lampung, 2024)
The purpose of implementing memorization activities is to pay more attention to improving the competence of teachers and employees of SMP IT Al Banna. Then provide motivation and encouragement so that memorization activities are important to do including how to maintain them. In addition, it is to provide an explanation of the methods in memorizing the Qur'an, so that you can choose which method is suitable and fits your abilities. The method of this activity is to observe the memorization activities that have been running to find out the obstacles and achievements, then provide training on more effective memorization methods and methods. Based on the implementation activities that have been carried out, it can be concluded that providing motivation and explanations about various memorization methods has a positive influence in terms of the quantity and quality of memorization, including motivation to maintain memorization better